Short-term price effects of a carbon tax and implications for sectors competitiveness in small open economies - Nicolas Gonne (Center for Economic Studies and ifo Institute (CESifo), 2010)
Asymmetric climate policies are expected to distort the level-playing field regarding international trade, singularly to the detriment of small open economies. The paper develops a flexible method that provides essential input regarding the design of offsetting measures. It builds on input-output analysis and standard input-output data to provide proxies for both carbon-intensity and trade-intensity. These are used to reckon the impact that such policies like carbon taxation are expected to have on international competitiveness. The method is then applied to the case of Belgium.
Keywords: C67; D57; H23; Q56; Q58; 330; carbon taxes; input-output analysis; sectors price-competitiveness; Ökosteuer; Steuerwirkung; Input-Output; Branche; Internationaler Wettbewerb; Kleines-offenes-Land; Schätzung; Belgien